2021
DOI: 10.3390/antiox10071044
|View full text |Cite
|
Sign up to set email alerts
|

Olive Polyphenols: Antioxidant and Anti-Inflammatory Properties

Abstract: Oxidative stress and inflammation triggered by increased oxidative stress are the cause of many chronic diseases. The lack of anti-inflammatory drugs without side-effects has stimulated the search for new active substances. Plant-derived compounds provide new potential anti-inflammatory and antioxidant molecules. Natural products are structurally optimized by evolution to serve particular biological functions, including the regulation of endogenous defense mechanisms and interaction with other organisms. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 173 publications
1
93
0
Order By: Relevance
“…It is indisputable that the antioxidant effects play a fundamental role in the effects of the studied compounds, and there are other mechanisms that possibly participate, such as the anti-inflammatory effects [ 26 ]. As can be seen in Table 3 , except for those of DHPG, there is a parallel between the IC 50 values for the inhibition of lipid peroxidation and the formation of peroxynitrite and LDH efflux.…”
Section: Discussionmentioning
confidence: 99%
“…It is indisputable that the antioxidant effects play a fundamental role in the effects of the studied compounds, and there are other mechanisms that possibly participate, such as the anti-inflammatory effects [ 26 ]. As can be seen in Table 3 , except for those of DHPG, there is a parallel between the IC 50 values for the inhibition of lipid peroxidation and the formation of peroxynitrite and LDH efflux.…”
Section: Discussionmentioning
confidence: 99%
“…Olive oil phenolics have been extensively studied for their potential to counteract the onset and progression of a variety of chronic and aging-related diseases, and is attributed to hypoglycemic, anti-obesity, cardioprotective, neuroprotective, antimicrobial, and anti-cancer properties [ 47 , 48 , 49 ]. Several in vitro and in vivo studies have associated the health-promoting effects of olive oil phenolics to their antioxidant and anti-inflammatory potential as related to their ability to modulate a series of molecular pathways.…”
Section: Olive Oilmentioning
confidence: 99%
“…Additionally, in vitro and animal studies have reported that oleuropein and hydroxytyrosol may reduce fat tissue accumulation by downregulating the expression of adipogenesis-related genes like PGC-1α, lipoprotein lipase, acetyl CoA carboxylase-1, and carnitine palmitoyltransferase-1 [ 54 ]. Recent reviews can be consulted for further information on olive oil phenolic effects and mechanisms of action [ 44 , 47 , 49 , 55 , 56 ].…”
Section: Olive Oilmentioning
confidence: 99%
“…They are classified as either flavonoid (anthocyanins, flavones, flavonols, flavanones, flavanols, and isoflavones) or non-flavonoid (stilbenes, lignans, tannins, phenolic acids, and hydroxycinnamic acids) [ 66 ]. Polyphenols exert positive effects and have a broad spectrum of biological activities against many human diseases such as type-2 diabetes mellitus, cancer, cardio-metabolic diseases, and neurodegenerative diseases, as well as having potential to modulate gut dysbiosis ( Figure 3 ) [ 67 ]. However, due to the extensive metabolism by phase-I and II enzymatic reactions and poor absorption, their bioactivity on targeted organs is significantly less.…”
Section: Polyphenolsmentioning
confidence: 99%